Textile Solid Waste Reutilization as a Support for Photocatalysts in the Treatment of Effluents Containing Dyes - Savoia, Jaqueline Elisabete Campelo; Marques, Rubiane Ganascim; Ribeiro, Valquíria Aparecida dos Santos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Textile industrial processes generate significant volumes of waste throughout the production cycle. A substantial portion of solid waste is not reused or recycled, leading to irregular disposal. In addition to solid waste, effluents from textile processing/finishing stages pose challenges for degradation due to the presence of complex and recalcitrant contaminants. These effluents contain challenging-to-degrade substances such as dyes and dyeing auxiliaries that are difficult to handle by conventional methods; an alternative to solving the problems is the use of Advanced Oxidative Processes (AOPs). Heterogeneus photocatalysis is a AOP that employs ultraviolet radiation in the presence of a catalyst to generate hydroxyl radicals capable of degrading compounds, including textile dyes. Despite its promise for industrial application, an impediment factor is the recovery of the catalyst in liquid medium. It is necessary to explore different support materials for catalyst immobilization. Considering the amount of solid waste in textile industries, this study proposes the use of fabric scraps as a support material, enhancing reusability and simplifying the photocatalytic process. The present study demonstrates the immobilization of TiO2/CeO2 catalysts on synthetic fabric scraps using an industrial blower, applied to heterogeneous photocatalysis promoting an efficient and sustainable solution for the removal of dyes. The effects of impregnation on different fabric scraps were evaluated varying the pH, and obtaining positive results for the photocatalysis of the commercial dye royal blue TIAFIX MER, achieving a 60% color removal, making the immobilized catalyst viable without the need for separation processes.